Spontaneous spinal subdural haematoma in a patient on apixaban. Issue 1 (22nd January 2019) - Mchaourab, Ahmad; Evans, Gwenllian Ying-Huey Rees; Austin, Richard
Abstract : A 68-year-old man on apixaban presented to the emergency department with back pain following a long-haul flight. Investigations for pulmonary embolus and aortic dissection were negative and he was discharged with analgesia for mechanical back pain. He presented three more times with worsening back pain, third time with urinary retention and the fourth time with lower limb weakness and loss of coordination. He was found to have a spinal subdural haematoma on MRI and transferred to a tertiary centre, where he was managed conservatively and discharged for rehabilitation with good neurological recovery.